How games induce cooperation? A study on the relationship between game features and we-intentions in an augmented reality game. (December 2017) - Morschheuser, Benedikt; Riar, Marc; Hamari, Juho; Maedche, Alexander
Abstract: Seamless cooperation between individuals is essentially a crucial aspect of any successful endeavor. A host of literature has been published in the academic realm about how cooperation could be cultivated. However, true cooperation often forms organically without external enforcement. Recently, there has been one special example of a context where cooperation seemed to have effortlessly sprung up between people who might not even have had previous connections. The context is video/online games ; games such as Ingress, Pokémon Go, and World of Warcraft bind people together to work against insurmountable odds and to overcome jointly held challenges. Organizations of many types have recently begun to gamify their structures and services in order to cultivate such seamless cooperation. However, before this potential of games can be successfully wielded outside video games, we need to understand better how games are able to cultivate such cooperation. Therefore, in this study we investigate how games can induce and cultivate we-intention of working as a group. Specifically, we investigate how cooperative game features affect different forms of group dynamics and how they further translate into we-intentions. We employ data from users of the augmented reality game Ingress (N = 206). The results show that cooperative game features induce we-intentions via positively increasing group norms, social identity, joint commitment, attitudes toward cooperation, and anticipated positive emotions. The findings imply that practitioners who are looking to increase cooperation should find that gamification inspired by cooperative game design is beneficial and preferable over individual-based gamification efforts. Graphical abstract: Highlights: Players' use of cooperative game features is associated with we-intention. This association is mediated by group dynamics: group norms, social identity, joint commitment, attitudes and anticipated emotions. Overall, players' use of single player features was not associated with we-intentions. Features of cooperative games can support practitioners cultivating cooperation.